Assessment of Development Results - Paraguay - United Nations Development Programme (United Nations, 2012)
This report on Paraguay’s Assessment of Development Results (ADR) focuses on the following three thematic areas: fostering democratic governance; achieving the Millennium Development Goals (MDGs) and reducing poverty under a human development perspective; and ensuring environmental sustainability. Reflecting on the characteristics of Paraguay’s economic history, its current juncture and prospects, the ADR examined the past with a forward-looking perspective.